Fahr’s disease: a rare neurodegenerative disorder - Ahmad, K; Dhungel, K; Sah, P; Ansari, S; Shashikar, Dr. (Health Renaissance, 2012)
Fahr's disease is a rare neurodegenerative disorder that is characterized by the bilateral symmetrical deposition of calcium in the basal ganglia, thalamus, dentate nuclei and centrum semiovale in the absence of hypoparathyroidism. It is often familial. Hereby, we are reporting a rare case of Fahr's disease who presented with repeated episodes of seizures and was diagnosed as Fahr's disease after performing computed tomographic (CT) scan. DOI: http://dx.doi.org/10.3126/hren.v10i2.6589 Health Renaissance 2012; Vol 10 (No.2); 155-156